Percepções sobre a prática docente e sentimentos dos professores de ciências e matemática durante a pandemia : uma análise à luz do TPACK - Teixeira, Luana Correia de Melo (2021)
COVID-19, a disease that quickly spread worldwide, became a pandemic and deeply affected daily life. Due to the measures needed to control the virus dissemination, such as social isolation and lockdown, schools were closed and an emergency remote teaching model was adopted. Teachers faced a completely unfamiliar model with a plethora of challenges: social inequality, lack of access to technologies and inadequacy of internet connection. Therefore, this research aims to understand, through TPACK (Technological Pedagogical Content Knowledge), science and mathematics teacher’s perceptions, feelings and adjustments on their teaching practice during the COVID-19 pandemic. The method chosen for this research was a qualitative case study with Brazilian basic education teachers of science and maths. Data was collected initially through a survey and later on semi structured interviews held with the teachers. Data investigation was performed through the lenses of TPACK applying Discursive Textual Analysis. Three main categories were formed by data analysis: (1) Teachers’ perceptions on school management, (2) Teachers’ perceptions on their teaching practice, and (3) Teachers’ perceptions on students. The result yielded by analysis of surveys and interviews demonstrate disparities between public and private education regarding infrastructure, technical support to teachers, qualification availability, and flexibility and agility on decision-making. Moreover, the adoption of remote teaching model highlighted the difficulty to access and use digital technologies, as well as a perceived effect on students and teachers’ mental health.